Violação dos direitos da criança e adolescente : análise de sete anos em um estado no sul do Brasil - Imado, Mayara Keiko (2017)
The present study had as objective to analyze the violation of rights of children and adolescents in the state of Paraná, in the period from 2009 to 2015. Descriptive, cross-sectional and retrospective research, with spatial analysis techniques, using secondary data regarding the violation of rights against children and adolescents in the state of Paraná. The data was collected through the Childhood and Adolescence Information System (SIPIA - Sistema de Informação para a Infância e Adolescência) between May 30th and July 27th of 2016. The descriptive data analysis and the spatial distribution of the violation of rights in Paraná were elaborated by making use of the software GeoDa version 0.9.5-i. The spatial autocorrelation was calculated using Global Moran s I (univariate and bivariate) and elaborated choropleth maps. Results: The rights violator agent I (relatives and people that live with the family) was the most prevalent (41,92%). The nuclear family (father, mother, stepfather, stepmother, siblings and guardian) was the predominant rights violator agent (88,67%), showing congruency with the main violated right: family and community coexistence, amounting to 41,02% of the cases. The rates of rights violation of children and adolescents were high (42,57) and (57,62) when compared to the rates of interpersonal/self-inflicted violence obtained in the Injury Report Information System (SINAN - Sistema de Informação de Agravos de Notificação), (11,39) and (12,32) respectively. Although the absolute data indicates a higher frequency of violation of children rights, the specific rates of violation were higher among the adolescents, indicating vulnerability in both age groups. The univariate analysis showed positive spatial autocorrelation, I= 0,189344 for children and I= 0,231207 for adolescents with p ≤ 0,05, indicating that counties with high rates of violation of rights of children and adolescents do not present a random distribution, being surrounded by counties also with high rates of violation of rights of children and adolescents. The clusters high-high and low-high of rights violation of both children and adolescents are concentrated in the South and Middle West regions of State. There was significance between the rates of violation of rights of children and adolescents and the socioeconomic variables: Illiteracy, Gini Coefficient, income and degree of urbanization. The results show that the violation of rights of children and adolescents is strongly present in the society of Paraná, despite the current legislation. It was observed yet difficulties and frailties of the Childhood and Adolescence Information System (SIPIA) and the underreporting in many counties even with the presence of Guardian Councils.